The effect of compound exercises on developing the performance art of handling skills for youth in handball: Applied research, Master's thesis, University of Sulaymaniyah, 2016 - عمر, داكان بختيار; نوري, آراز محمد (Sulaimani Journal for Humanities, 2025)
As for the research methodology and field procedures, the experimental method was used to suit the nature of the research problem by using the experimental design of two groups (experimental and control). The research community was identified from the schools of Sulaymaniyah Club and the new Sirwan Club. (24) players from the school of Sulaymaniyah Sports Club and (20) players from the school Club Sirwan new sports and we have determined the sample of the research in a deliberate way from the school of Sulaymaniyah Sports Club to provide the appropriate training room where the percentage (54.54%) of the original research community and our players divided into two groups (experimental and control) by (10) players for each group in the random way after the exclusion of (2) two goalkeepers and the use of 2 players for the two trials and then conducted the main experiment (exercise) (8/5/2016 - 30/6/2016) for 8 weeks with (3) educational units per week ie (24) educational units. Educational unit (60-70) minutes. We have relied on the appropriate statistical means to deal with data obtained from tribal and remote tests in order to obtain the differences between the computational settings of the tribal and remote tests of each group. We also relied on other laws to reach the final results of the research. One of the most important conclusions we have reached is that the use of complex exercises within educational units has a positive effect on the development of skilled performance (handling from head level, jumping handling)